VISUAL ANALYSIS OF LEE JEFFRIES’ INSTAGRAM PHOTOGRAPHS - Prasetyo, Martinus Eko; Everlin, Shierly; Winnie, Winnie (Seni Media Rekam ISI Surakarta, 2022)
Instagram is a social media platform for publishing photographic works. Lee Jeffries, one of the most renowned portrait photographers, consistently exposes his works to the general public, including through the social media platform Instagram. His photographic works are considered highly interesting and unique due to their capacity to transmit social messages. Lee Jeffries consistently captures photographs of homeless people worldwide to convey social messages to his audience. This motivates the authors to discuss the meaning of visual messages in Lee Jeffries' works. The study employed a qualitative descriptive approach to analyze the photographs’ composition, color, and symbolic meaning. The results show that the application of symmetrical and asymmetrical compositions and colors for portraits of human faces, especially those of the homeless on urban street corners, produced symbolic meanings, including sadness, emotion, and happiness.Instagram is a social media platform for publishing photographic works. Lee Jeffries, one of the most renowned portrait photographers, consistently exposes his works to the general public, including through the social media platform Instagram. His photographic works are considered highly interesting and unique due to their capacity to transmit social messages. Lee Jeffries consistently captures photographs of homeless people worldwide to convey social messages to his audience. This motivates the authors to discuss the meaning of visual messages in Lee Jeffries' works. The study employed a qualitative descriptive approach to analyze the photographs’ composition, color, and symbolic meaning. The results show that the application of symmetrical and asymmetrical compositions and colors for portraits of human faces, especially those of the homeless on urban street corners, produced symbolic meanings, including sadness, emotion, and happiness.